Activation of Elemental Sulfur by Aluminum Dihydride: Isolation of Mono‐ and Bis(hydrogensulfide) Complexes of Aluminum. Issue 34 (22nd April 2014) - Franz, Daniel; Inoue, Shigeyoshi
Abstract The conversions of the dimeric imidazolin‐2‐iminato aluminum dihydride {μ‐LDippAlH2}2 (1) with 1/4 or 1/2 equivalents of S8 gave the elusive hydrogensulfide {μ‐LDippAl(H)SH}2 (2) and the bisthiol {μ‐LDippAl(SH)2}2 (3), respectively (LDipp=NC(N(Dipp)CH)2, Dipp=2, 6‐diisopropylphenyl). Notably, these transformations proceeded in the absence of a promoter. The reaction of {μ‐LMesAlH2}2 (4), a less bulky congener of 1, with phenyl disulfide produces the phenyl sulfide {μ‐LMesAl(H)SPh}2 (5; LMes=NC(N(Mes)CH)2, Mes=2, 4, 6‐trimethylphenyl). The hitherto unknown compounds 2–5 were characterized by using spectroscopic methods and single‐crystal X‐ray diffraction analysis.